“สักยันต์”: การกลายเป็นโครงสร้างพื้นฐานทางความเชื่อของคนเวียดนาม (บางกลุ่ม) ในปัจจุบัน : “Sak Yant”: An infrastructure of some Vietnamese belief today - ตี่ขันติกุล ศิลปกิจ (Journal of Humanities and Social Sciences (HUSOKKU), 2023)
Abstract This research paper aims to study Thai Sak Yant as infrastructure of belief of some Vietnamese people today. By using ethnography research methodology, participatory observation and informal interview, to collect data from various "actors" that are human, non-human and object/thing both in online and offline life. In addition, the researcher has chosen to use the concept of "infrastructure" of Star (1999) as an analysis framework. The research found that Vietnamese tradition of tattoo has existed since 2000-3,000 years ago. Later, during the Trần dynasty (1225-1400 AD), the royal court issued rules for tattooing. Untill the reign of King Trần Anh Tông (1293-1314 AD), he issued a decree repealing the rules that making body tattoos to be a personal matter. While Thai sak yant has spread to Vietnam society since the year 2012, beginning with the Vietnamese star named Ngô Thanh Vân travels to do sak yant 5 rows with ajarn Nu (Kanpai) at Thailand that became a famous news in the current Vietnam newspaper. Today, Thai sak yant has become popular among people in Vietnam, both in online and offline life. This result occurs from a process of linking/working together of each “infrastructure”. That starting with (1) Internet network as infrastructure for communication, allowing Vietnamese people quickly and widely access information/knowledge about Thai sak yant. And become online products of sak yant trader through "Facebook". (2) International transportation network as infrastructure of transportation, helping ajarn sak yant travel to Vietnam quickly and conveniently and Vietnamese people have access to goods /objects (yant) easily and quickly as well. (3) Sacred network (yant) as infrastructure of belief, helping Vietnamese people to access; power, prestige, mercy, great popularity, wealth, money, fortune, success in work, great charm, love. Finally, Thai sak yant has become (new) infrastructure of belief of some Vietnamese in Vietnam society today. Keywords: Sak Yant, Infrastructure of belief, Vietnamese, Vietnam society